Incidence of New, Nonphysiologic Maternal Findings on Fetal Magnetic Resonance Imaging - Shao, Shirley J.; Grimes, Andrew; Rashad, Marley; Poder, Liina; Shum, Dorothy; Sobhani, Nasim C. (American Journal of Perinatology, 2024)
Fetal magnetic resonance imaging (MRI) is increasingly used for evaluation of fetal anomalies, and rates of incidental maternal findings are not well characterized. Our objective was to evaluate the rate of incidental maternal findings at the time of antenatal MRI performed for fetal indications.This was a retrospective cohort study that included all fetal MRIs performed between 2018 and 2023 at a single tertiary care institution with a multidisciplinary fetal diagnosis and treatment center. The electronic medical record was reviewed to identify all documented maternal findings and any new, nonphysiologic maternal findings. The latter was defined as previously unknown abnormalities of maternal structures unrelated to normal physiology.Our study included 834 imaging events, performed at an average gestational age of 23 weeks. The most common indication for imaging was fetal anomaly (81.1%). The most common imaging type was fetal brain MRI (81.4%). Overall, 16.2% reported a maternal finding and 7% reported a new, nonphysiologic finding. The most common new, nonphysiologic findings were renal cysts (n = 11), liver cysts (n = 6), and gallstones or gallbladder sludge (n = 5). Compared with imaging events that included a fetal brain MRI, imaging events that included a fetal body MRI had a significantly higher rate of any maternal findings (53.0 vs. 10.4%, p < 0.001) and new, nonphysiologic maternal findings (26.9 vs. 3.7%, p < 0.001).Our results suggest that the risk of identifying new, nonphysiologic maternal findings on fetal MRI is low. The rate of any maternal and new, nonphysiologic maternal findings may differ by fetal MRI type due to differences in imaging depth and extent of radiology subspecialist review. These data should be incorporated into pretest counseling for patients planning to have fetal MRI.
Keywords: fetal imaging; incidental finding; incidentaloma; obstetrics